Comparative study of permanent magnet-synchronous and permanent magnet-flux switching machines for high torque to inertia applications - Al-Timimy, A.; Giangrande, P.; Degano, M.; Galea, M.; Gerada, C. (2017)
This paper investigates the capability of both permanent magnet synchronous machine (PMSM) and permanent magnet flux switching (PMFS) machine to provide high torque to inertia ratio for applications with demanding response in terms of acceleration and fast dynamic. The PMSM has higher torque density and efficiency among different electrical machines. However, the presence of the permanent magnets can increase the rotor inertia. Thanks to its passive salient-pole rotor, PMFS machine is a suitable solution for those applications requiring lower inertia. This paper provides a comparative analysis between the PMSM and PMFS machines considering the torque to inertia ratio, the challenges of a flooded air gap and dimensional constraints. The electromagnetic performances of both machines have been evaluated by means of finite element method and a detailed sensitivity analysis is carried out for stator and rotor geometry.